Acute medical stabilisation of adults with anorexia nervosa: experience of a defined interdisciplinary model of care. Issue 1 (14th January 2020) - Braude, Michael R.; Con, Danny; Clayton‐Chubb, Daniel; Nandurkar, Ruchira; Chua, Ling‐Ern; Newnham, Evan D.
Abstract: Background: Patients with anorexia nervosa (AN) are vulnerable to physiological decompensation and often require inpatient management by an eating disorders unit. Aims: Patients admitted to an Australian tertiary medical centre for medical stabilisation of AN were assessed as part of quality assurance. Analysis included: (i) medical complications during acute inpatient stabilisation; (ii) predictors of refeeding syndrome; (iii) predictors governing length of stay (LOS); and (iv) outcomes pre‐ and post‐implementation of multidisciplinary treatment guidelines. Methods: A retrosepctive analysis of 95 consecutive admissions (60 individual patients) between November 2011 and August 2017 was performed. Results: Patients had a median LOS of 9.6 days (interquartile range 5.8–19.7) and a mean weight gain of 1.4 kg (standard deviation 2.9). Medical complications included the following: hypoglycaemia (11.6%) and refeeding electrolyte derangement (26.3%). Advancing age (odds ratio (OR) 1.06 per year, P = 0.019), nasogastric tube requirement (OR 3.4, P = 0.014) and Code Grey(s) (security calls) (OR 7.1, P = 0.010) were associated with refeeding electrolyte derangement. Parameters associated with increased LOS included the following: lower body mass index ( P = 0.029), Code Grey(s) ( P = 0.029) and tachycardia ( P = 0.013). Following multivariate analysis, the post‐guidelines implementation group required less intravenous fluid and electrolyte replacement, though had lower rates of refeeding electrolyte derangement (OR 0.33 (0.11–0.99)). Conclusion: Patients with moderate to severe AN are at risk of dangerous medical complications, and older patients may have heightened predisposition to refeeding electrolyte derangement. Early identification of medically high‐risk patients is imperative to implement timely, life‐saving interventions.